RNA extraction from urine sediment: A cost-effective protocol for gene expression analysis in renal pathology. - Saseevan, S.; Rajapakse, S.; Magana-Arachchi, D.N. (Ceylon Journal of Science, 2020)
Urine is an appropriate choice of specimen to study the biomarkers for metabolic and renal disorders because it is readily available with less harm to the patients. However, RNA extraction from voided urine is challenging due to the presence of RNases and cell scarcity. This study aims to optimize a protocol for RNA extraction from urine samples for gene expression studies in renal pathology. Hundred and two urine samples were collected from both healthy controls (HC) (𝑛 = 15; 54 ± 11 years) and chronic kidney disease (CKD) patients (𝑛 = 87; 56 ± 10 years) and centrifuged at 6,500 ɡ for 20 min at 4 °C to obtain sediment. RNA was extracted from urine sediments using a phenol-based technique. The extracted RNA was quantified and reverse-transcribed into complementary DNA (cDNA). Reverse transcriptase quantitative polymerase chain reactions (RT- qPCR) were carried out using 2 ng of template cDNA to amplify the housekeeping gene, β2- microglobulin (B2M). The total yield of RNA from CKD and HC samples were 718 ± 164 ng and 790 ± 231 ng, respectively, and a statistically significant difference was not observed between the two study groups (p > 0.05). The urinary RNA recovery was significantly increased with CKD progression (p < 0.05). Further, the results show that urine volume, gender, and serum creatinine level significantly influence the RNA yield in only disease groups (p < 0.05). The mean threshold cycle (Ct) values for B2M amplification of CKD and HC were 27.36 ± 3.09 and 20.97 ± 3.90, respectively. This modified phenol-chloroformbased urinary RNA extraction method is less expensive and does not require pre- and post-purification steps. It provides a higher yield of RNA with less inhibition to qPCR and is sufficient for downstream applications than column-based techniques.
Keywords: Chronic kidney disease; cDNA synthesis; Gene expression; RNA extraction; RT-qPCR